2018
DOI: 10.1016/j.jalz.2018.06.3057
|View full text |Cite
|
Sign up to set email alerts
|

A nonhuman primate model of early Alzheimer's disease pathologic change: Implications for disease pathogenesis

Abstract: Introduction: Nonhuman primates may serve as excellent models of sporadic age-associated brain β-amyloid deposition and Alzheimer’s disease pathologic changes. We examined whether a vervet nonhuman primate model recapitulated pathologic, physiologic, and behavioral features of early Alzheimer’s disease. Methods: Nine middle-aged (mean = 11.2 years) and nine aged (mean = 21.7 years) female vervet/ African green monkeys underwent cerebrospinal fluid collection, gait speed measurement, and neuroimaging before n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
105
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 50 publications
9
105
2
Order By: Relevance
“…Paspalas et al (76) described recently AD-like tau pathology in an aged rhesus monkey, including the presence of NFTs observed using electron microscopy and autophagic vacuoles reflective of neuron death. Others have described the presence of AD-like NFTs in aged African green monkeys (77,78). These Old World anthropoid species are valuable models for tracking ADlike pathology at the biochemical/histochemical level and suggest that the molecular machinery for NFT formation may exist across primate species.…”
Section: Discussionmentioning
confidence: 99%
“…Paspalas et al (76) described recently AD-like tau pathology in an aged rhesus monkey, including the presence of NFTs observed using electron microscopy and autophagic vacuoles reflective of neuron death. Others have described the presence of AD-like NFTs in aged African green monkeys (77,78). These Old World anthropoid species are valuable models for tracking ADlike pathology at the biochemical/histochemical level and suggest that the molecular machinery for NFT formation may exist across primate species.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, research in monkeys has played, and can continue to play, a vital role in revealing the etiology of LOAD. Although this review has focused on research from aging rhesus monkeys, studies of other primate species, such as African green monkeys (34,96) and marmosets (97), can expand our knowledge of how the aging association cortex becomes vulnerable to LOAD-like pathology. This view can complement existing strategies using canine models (98) and mouse models to produce a more comprehensive understanding of LOAD etiology.…”
Section: Future Directions: Transgenic Monkeysmentioning
confidence: 99%
“…While substituting the AT8 pTau capture antibody with the AT270 antibody allowed detection of pTau in aged vervets and mutant C. elegans strains, it is possible that additional modifications of the original assay format could still permit Luminex-based quantification of AT8 reactive pTau in those samples. It has been observed that application of NIA-AA guidelines to the analysis of aged vervets identified only 'not' and 'low' AD neuropathologic change [12]. A comprehensive analysis of pTau in the dog brain by immunohistochemistry found marked hyperphosphorylation of Tau in only three out of 24 study dogs, only one of these three dogs was a small dog comparable to the breeds used in our investigation [13].…”
mentioning
confidence: 61%
“…While some studies were able to detect AT8-reactive pTau or pTau (Ser396) in dog brains [14,15], others could not detect AT8-reactive pTau in dog brains [16,17]. Similarly, some studies report AT8reactive pTau in aged vervets [12], others detected either no or different pTau epitopes in rhesus monkeys or marmosets [18,19]. It will be of interest to apply our current investigation not only to larger samples, but also to additional species, for example cats [20], that could be used as novel alternative models for the study of AD neuropathologic change.…”
mentioning
confidence: 99%